Logic for the Decalogue - Gerogiorgakis, Stamatios (Sophia, 2014)
In this article, I offer two different formalizations for prescriptions which correspond to two different forms of biblical prohibitions. I discuss the known fact that the prohibitive commandments of the Decalogue according to the Septuagint and the Vulgate, Exodus 20 and Deuteronomy 5, are formulated with normative future tense indicatives. However, the Greek and Latin sources provide in Mark 10:19 variants of five biblical prohibitive commandments which are formulated with prohibitive subjunctives. I argue that there are semantic differences between normative future tense indicatives and prohibitive subjunctives. These semantic differences are of importance for the understanding of the Decalogue.